2019
DOI: 10.3847/1538-4357/ab1f6b
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence and Particle Acceleration in Collisionless Magnetic Reconnection: Effects of Temperature Inhomogeneity across Pre-reconnection Current Sheet

Abstract: Magnetic reconnection is an important process in various collisionless plasma environments because it reconfigures the magnetic field and releases magnetic energy to accelerate charged particles. Its dynamics depend critically on the properties of the pre-reconnection current sheet. One property in particular, cross-sheet temperature inhomogeneity, which is ubiquitous throughout the heliosphere, has been shown to increase reconnection outflow speed, energy conversion efficiency, and secondary island formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 111 publications
4
32
0
Order By: Relevance
“…(2019), Lu, Angelopoulos, et al. (2019) found that the strong temperature inhomogeneity in a current sheet further increases reconnection outflow speed, causing numerous secondary islands to be formed continuously at reconnection X‐lines. Secondary islands have also been observed by satellites in different regions (Wang et al., 2010, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…(2019), Lu, Angelopoulos, et al. (2019) found that the strong temperature inhomogeneity in a current sheet further increases reconnection outflow speed, causing numerous secondary islands to be formed continuously at reconnection X‐lines. Secondary islands have also been observed by satellites in different regions (Wang et al., 2010, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…On the other hand, the role of turbulence associated with reconnection has received significant scrutiny. Reconnection is known to generate several secondary instabilities (e.g., 7,12,25,49 and references therein) which themselves have been shown to generate energy spectra with power laws consistent with a turbulent cascade 26,31,37 . Turbulent fluctuations in the plasma flowing into the reconnection region have been found to affect the process of reconnection 30 , and even amplify the reconnection rate 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The PSDs of the ideal‐MHD (orange lines) and Hall‐MHD (green lines) simulations are also plotted for comparison, and neither of them shows the 2.8 slope. The evolution of the small‐scale secondary magnetic islands is another mechanism that produces a power law spectrum (Lu et al, 2019). Since our simulation does not capture small‐scale reconnections in the magnetosheath (Phan et al, 2018) and the secondary islands along the magnetopause are not produced frequently, the PSDs in Figure 4 are not likely related to the secondary magnetic islands.…”
Section: Simulation Results and Comparison With Observationsmentioning
confidence: 99%